Factors Affecting the Concentration of Learning and Critical Thinking on Student Learning Achievement in Economic Subject - Erwiza, Erwiza; Kartiko, Sri; Gimin, Gimin (Journal of Educational Sciences, 2019)
The National Examination is conducted to test the ability of students during the education process. However the average national exam results of Madrasah Aliyah Negeri 1Pekanbaru starting from 2015-2018 always decrease. This phenomenon can not be separated from factors that affect learning achievement. This study aims to analyze thefactors that influence concentration and critical thinking on student learning achievement both direct influence and indirect influence on economic subjects in Madrasah Aliyah Negeri 1 Pekanbaru (MAN 1 Pekanbaru). The population in this study were 125 students of IIS class XI. Sampling technique used was simple random sampling obtained by 95 students. Data collection uses a questionnaire with a Likert scale. The results showed that: (1) the non-physical school environment had an effect on learning achievement directly by 24.2% and indirectly had an effect of 12%. (2) learning interest influences learning achievement directly by 27.1% and indirectly by 8.8%. (3) learning concentration directly affects learning achievement by 19.5%. (4) critical thinking directly influences learning achievement by 27.3%. In general, critical thinking can affect the learning achievement.